The Importance of Seeking Truth: Lessons from al-Ghazali - Prasetia, Senata Adi (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2023)
This article critically examines how al-Ghazali carries out the process of seeking truth and its contextualization in contemporary Indonesian Islam. al-Ghazali entered a deep crisis because of his doubts about the senses and reason and described this state as